KONSEPSI AKHLAQ DAN STANDARISASI DALAM PENILAIANNYA - Ismail Anas (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
Allah has given Islam through Prophet Muhammad to free the human mind from the pressures of the science of divinity (Tauhid) during the fool era, to give the power of attitude to the human in the world, therefore God created the Prophet Muhammad in the form of a perfect and best of all God’s creation on earth, Ahlaqul karimah is a state of soul which it must be good, which can occur spontaneously in the attitude of polite (respectable) without much thought or consideration. Behavior/attitude can not be said as akhlaqul karimah when humans only use the mind (can differentiate between good and bad) without applying the behavioral attitude of Man. Civility, Shara (Al-Qur’an and Sunnah) can be used to measure or evaluate human action and human behavior when a man can be called good or bad, this measurement refers to the theoretical basis of the standards of the Akhlaqul karimah, if we judge akhlaqul karimah using feelings, thoughts, and opinions of our society will not be able to find the correct sense in understanding the definition Akhlaqul karimah widely and generally. This article provides basic concepts about akhlaqul karimah and its measurement.